The Obligation to Tear Through the Veil: An Analysis and Transformation of Mankind’s Insufficient Complacency Through the Novels of Jenny Offill - Toole, Maggie (Meliora, 2022)
This thesis explores the ways in which we as humans are alienated by the fundamental social structures of our world and how the novels of Jenny Offill offer a possible remedy. With a specific focus on the psychological and evolutionary aspects of womanhood and motherhood, this text attempts to illustrate the ways in which these novels address the imposing weight of such fundamental structures in the 21st century. Through an analysis of the nuclear family, this thesis examines the debilitating and profound existence of women, and more specifically, mothers. Offill’s novels present a profoundly clear picture of the modern world as it depicts the reality and ramifications of psychoanalytic and evolutionary theory. This work demonstrates how Offill’s texts attempt to remedy the core dissonance of our binary-laden human existence with clarity and realization rather than acceptance of an oversimplified past and a debilitating future.